Anxiety and Depression last one Month after Miscarriage at Jordan University Hospital - Basha, Asma; Abu Ghalyon, Insaf; El-Qudah, Malab; Elyyan, Yousef; Obeidat, Mohammed; Obeidat, Zaina; Alsalihi, Haya; Abu-Khader, Ilham (Jordan Journal of Pharmaceutical Sciences, 2021)
Background: Miscarriage is associated with moderate to high risk of psychological problems. In Arab countries, the percentage of people who seek psychological help is low. The epidemiological mental studies for clinical and community samples are not frequently conducted in Jordan. The purpose is to study the rates of anxiety and depression one month after miscarriage and compare them to rates immediately after miscarriage. Subjects and Methods: A cross-sectional sample of 200 women between June 2018 and December 2019with early pregnancy loss up to 13 weeks of gestation was studied. Assessment for the severity of anxiety and depression was carried out within 12 hours after miscarriage and one month later, using translated and validated versions of the Generalized Anxiety Disorder-7andthe Patients Health Questionnaire 9. Results: The mean age of women was 33.1± 6.3years and the age ranged between 19-47 years. The number of miscarriages ranged from 1-12 with a mean of 1.9 ± 1.5. Within 12 hours post evacuation; 19.5% of women had severe anxiety and 22.5% had moderately severe and severe depressive symptoms. One month later; 5.5% had severe anxiety and 7% had moderate to moderately severe depressive symptoms. Severe anxiety was transient in about 72% of women and moderate to severe depression was transient in 69%. Conclusions: Understanding the type and frequency of emotional reactions to pregnancy loss is important. Screening is advised to target appropriate support to those who need, there-by minimizing psychological morbidity and its societal cost. Increasing medical staff awareness is needed.